2005
DOI: 10.1016/j.anbehav.2004.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Colour biases are a question of taste

Abstract: Unpalatable insects often advertise their defences to avian predators by conspicuous colours, such as red and yellow. Therefore, perhaps not surprisingly, birds tend to have unlearned biases against warningly coloured food. These biases are particularly evident when other components of insect warning displays, such as novel sounds and odours, are also present. We tested whether bitter taste, often associated with the defensive chemicals used by aposematic insects, can elicit or enhance specific colour aversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…In fact, it has been suggested that trichromatic colour vision may originally have developed in primates as an adaptation that facilitated the selection of more energy-rich (and likely red) fruits from in-amongst the dark green forest canopy (e.g., Bompas, Kendall, & Sumner, 2013;Regan et al, 2001;Sumner & Mollon, 2000). Certainly, a complex interplay of animal signalling designed to capture the attention (often visual) of pollinators and/or repel predators has been a central part of the co-evolution of both the visual systems of animals and the colouration schemes utilized in both the animal and plant kingdoms (e.g., see Barth, 1985;Cott, 1940;Poulton, 1890;Rowe & Skelhorn, 2005;Schaefer & Schmidt, 2013).…”
Section: Introduction: the Brain And Foodmentioning
confidence: 99%
“…In fact, it has been suggested that trichromatic colour vision may originally have developed in primates as an adaptation that facilitated the selection of more energy-rich (and likely red) fruits from in-amongst the dark green forest canopy (e.g., Bompas, Kendall, & Sumner, 2013;Regan et al, 2001;Sumner & Mollon, 2000). Certainly, a complex interplay of animal signalling designed to capture the attention (often visual) of pollinators and/or repel predators has been a central part of the co-evolution of both the visual systems of animals and the colouration schemes utilized in both the animal and plant kingdoms (e.g., see Barth, 1985;Cott, 1940;Poulton, 1890;Rowe & Skelhorn, 2005;Schaefer & Schmidt, 2013).…”
Section: Introduction: the Brain And Foodmentioning
confidence: 99%
“…Alternatively (hypothesis 2), based on the neural convergence hypothesis [1] -vagal afferents mediating gustatory and visceral sensations -and the cue-consequence [19] and skin-gut specificity [20] of conditioning contingencies, we predicted blackbirds would avoid flavors previously paired with negative postingestive consequences. Finally, foraging biases [21] and baseline preferences affect conditioned avoidance (hypothesis 3). Thus, relative to preferred colors and flavors, we predicted that blackbirds would avoid colors and flavors for which baseline indifference or aversion existed.…”
mentioning
confidence: 99%
“…However, more recent studies have shown certain species of bird to respond to a number of taste stimuli, particularly bitter tastes in foodstuffs and solutions. 31,32 However, the marked delay in formation of preference observed in the present study is more indicative of a post-ingestive effect of food consumption than of a simple taste preference, where the response would likely be much more rapid. Taste is unlikely, therefore, to be driving the preference for conventional wheat in the current experiment.…”
Section: Differences In Physical Properties -Size Hardness and Tastementioning
confidence: 48%